Relationship between leadership development and leadership effectiveness, employee performance and employee satisfaction - Mehrabani, Shadi Ebrahimi (2013)
In spite of the fact that leadership development is one of the key factors for the success of an organization, there is still a lack of experiential evidence and systematic approach in leadership development. The main purpose of this study is to identify the leadership skills that need to be developed for an effective leadership development program. This study introduced seven leadership development skills by developing the following dimensions: inspiration of shared vision, environment of trust, communication, team work, creativity and problem solving, motivation in others by accrediting them and empowerment. Besides these skills, three factors were used to define effectiveness such as leadership effectiveness, employee satisfaction and employee performance. In addition, training and knowledge sharing were proposed as moderators in the relationships. Data were collected from managers of six private oil companies in Iran. Twenty three hypotheses were tested using Structural Equation Modelling and Stepwise Multiple Regression techniques. The results showed that developing inspiration of shared vision and communication skills contributed the most to leadership effectiveness. Statistically, developing creativity and problem solving, and empowerment, also influenced all the three factors of effectiveness. In fact, developing motivation in others by accrediting them had an influence on employees? satisfaction and performance. Training was discovered to be a moderator in the relationship between leadership development and effectiveness outcomes while knowledge sharing did not have any moderator effect. This study has identified variables that organizations can use to expand their leadership development programs.